2016
DOI: 10.15171/jrip.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiofrequency radiation in the presence of gold nanoparticles for the treatment of renal cell carcinoma

Abstract: Introduction: The most common type of kidney cancer is renal cell carcinoma (RCC), which accounts for more than 80% of all kidney cancers. Objectives: The aim of this study was to evaluate the effects of radiofrequency (RF) radiation in the presence of gold nanoparticles (GNPs) for the treatment of RCC. Materials and Methods: Human embryonic kidney (HEK) cancer cells were divided into 6 groups. Various tests were performed on HEK cells in the presence of RF and GNPs. In order to investigate the radiation eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…CW-AuNPs can reduce the level of Bcl-2 and thereby induce apoptosis of A498 cells ( Liu et al, 2019 ). Other studies have found that AuNP treatment reduces the viability of cancer cells, suggesting a potential alternative to nephrectomy ( Nikzad et al, 2017 ).…”
Section: Gold Nanoparticles (Aunps)mentioning
confidence: 99%
“…CW-AuNPs can reduce the level of Bcl-2 and thereby induce apoptosis of A498 cells ( Liu et al, 2019 ). Other studies have found that AuNP treatment reduces the viability of cancer cells, suggesting a potential alternative to nephrectomy ( Nikzad et al, 2017 ).…”
Section: Gold Nanoparticles (Aunps)mentioning
confidence: 99%
“…Hydrogel coating has also been used in vascular catheter access to reduce thrombus accumulation (Mannarino et al, 2020). Metallic nanoparticles such as gold, silver, and iron have also been used as drug carriers, mediator for ablation, or as an aid in radiofrequency radiation therapy (Nikzad et al, 2017).…”
Section: Nanotechnology Applications In Interventional Radiologymentioning
confidence: 99%
“…Moreover, GNPs are often used in photodynamic therapy (PDT) by generating heat to kill tumor cells ( Cabuzu et al, 2015 ). Nikzad et al (2017) assessed the effects of treatment of RCC with RF radiation in the presence of GNPs. Human embryonic kidney cells were subjected to various tests in the presence of RF and GNPs.…”
Section: Nanotechnology In Renal Cancermentioning
confidence: 99%
“…In vitro MTT assays showed that cell viability was dramatically reduced in the RF-treated groups in the presence of GNPs compared with that in the control group. Thus, this method may be suitable for the treatment of RCC, providing a new method for alternative nephrectomy ( Nikzad et al, 2017 ).…”
Section: Nanotechnology In Renal Cancermentioning
confidence: 99%